The Technical and Economic Study of Solar-Wind Hybrid Energy System in Coastal Area of Chittagong, Bangladesh - Podder, Shuvankar; Khan, Raihan Sayeed; Alam Mohon, Shah Md Ashraful (Journal of Renewable Energy, 2015)
The size optimization and economic evaluation of the solar-wind hybrid renewable energy system (RES) to meet the electricity demand of 276 kWh/day with 40 kW peak load have been determined in this study. The load data has been collected from the motels situated in the coastal areas of Patenga, Chittagong. RES in standalone as well as grid connected mode have been considered. The optimal system configurations have been determined based on systems net present cost (NPC) and cost of per unit energy (COE). A standalone solar-wind-battery hybrid system is feasible and economically comparable to the present cost of diesel based power plant if 8% annual capacity shortage is allowed. Grid tied solar-wind hybrid system, where more than 70% electricity contribution is from RES, is economically comparable to present grid electricity price. Moreover, grid tied RES results in more than 60% reduction in greenhouse gases emission compared to the conventional grid. Sensitivity analysis has been performed in this study to determine the effect of capital cost variation or renewable resources variation on the system economy. Simulation result of sensitivity analysis has showed that 20% reduction of installation cost results in nearly 9%–12% reductions in cost of per unit energy.